ANALISIS PENGUATAN BUDAYA SENYUM, SAPA, SALAM, SOPAN, DAN SANTUN (5S) TERHADAP PENDIDIKAN KARAKTER SISWA DI UPTD SD NEGERI 378 WELE KECAMATAN BELAWA KABUPATEN WAJO - Andi Hartati; Syamsiar; Tenri Sau (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strengthening of the culture of smiling, greeting, saluting, politeness, and courtesy (5S) in shaping students’ character education at UPTD SD Negeri 378 Wele, Belawa District, Wajo Regency, by positioning the school as a space for the habituation of living and contextual values, particularly within a rural socio-cultural environment. This study employs a qualitative approach with a case study design, using data collection techniques such as observation, in-depth interviews, and documentation involving the principal, teachers, and students as the primary data sources. Data analysis is conducted through a descriptive-interpretative method, encompassing data reduction, data display, and conclusion drawing, strengthened by triangulation techniques. The findings reveal that the strengthening of the 5S culture is not merely understood as a social habit, but has been internalized as a character education practice that shapes students’ religious attitudes, discipline, responsibility, and mutual respect. The uniqueness of the research setting is characterized by the close relationships between teachers and students, as well as the support of the local community’s cultural values surrounding the school, which serve as the main supporting factors for the successful implementation of this habituation. Interpretatively, these findings affirm that school culture based on simple habituation practices such as 5S holds strategic potential as an effective, contextual, and sustainable model of character education. Therefore, this study provides a theoretical contribution to the development of school culture–based character education studies, as well as a practical contribution as an implementative reference for elementary schools with similar characteristics.